Dynamics of spatial and ontogenetic structure of Cephalanthera rubra (Orchidaceae) populations in the east of European Russia (Middle Volga Region) - Marina B. Fardeeva; Nelli A. Chizhikova (Nature Conservation Research: Заповедная наука, 2023)
The assessment of the spatial and functional features of rare species populations without considering the ontogenetic groups, which are being rarely distinguished at international literature, does not give a complete understanding of the current status of populations and prospects of their development under various management conditions. This paper is aimed to determine the status of a threatened orchid species, Cephalanthera rubra, at the eastern border of its range (Republic of Tatarstan, European Russia). For this purpose, a complex of various population parameters was used. Ontogenetic groups of C. rubra individuals have been reliably identified on the basis of morphometric traits of reproductive and vegetative organs. The obtained results showed that the fruit set is low, ranging at average from 24% for young reproductive individuals (g1) to 39% for mid-mature reproductive individuals (g2); it reflects prospects for seed reproduction of this species at the eastern edge of its range. The abundance dynamics of populations has a fluctuation type; it is related to climatic factors of the growing season. So, we found its significant positive correlations with air humidity (from r = 0.6 to r = 0.7) and precipitation (from r = 0.5 to r = 0.6), and a negative correlation with temperature (from r = -0.5 to r = -0.6). In the Republic of Tatarstan, the base spectrum of C. rubra populations is of the centred type, 1:10:51:38 (j:im:v:g); it corresponds to the general ontogenetic spectrum of rhizomatous orchids. The spatial-ontogenetic structure of populations, and especially its dynamics, reflects the intraspecific relationships of various ontogenetic groups involved in maintaining the stability of C. rubra population in space and time. Under optimal conditions, the spatial structure of all individuals and reproductive groups is characterised by a spatial randomness, which probably reduces intraspecific competition. In contrary, pre-reproductive groups form aggregations with 0.5–0.9-m radius in microloci, favourable for seed germination. A characteristic feature of the spatial structure is the formation of aggregations of reproductive and pre-reproductive individuals with a 0.7–1.0-m radius with a 0.2–0.4-m zone of the random spatial positioning of individuals, which aims to reduce intraspecific competition between them. The probability of meeting an individual of another ontogenetic group increases towards the periphery of the formed aggregation. In C. rubra populations, the abundance and density of individuals, and the fruit set decrease in pessimal conditions of landslides, soil erosion, and habitat shading. Under these conditions, pre-reproductive individuals do not form aggregations, nor aggregations with reproductive individuals. In general, the spatial structure of a population depends on the life-form type of the species, the mechanism of spatial growth of underground organs; it is considered a diagnostic sign of the population status.